Wydatki publiczne a rozwój gospodarczy Polski - Stawicka, Magdalena; Kędzierska, Małgorzata (Public Expenditures versus Economic Development, 2007)
This article focuses on one of the most important categories of budget - public expenditures. What should be the appropriate structure of contributions to economic development? Is it possible to set a permanent level of this category? This article is an attempt to answer these questions through discussing of influence of public expenditures on socio-economic situation in Poland and presenting a good way on the basis of Ireland's experiences. Public expenditures are necessary, even in the context of liberal economic theory. The state has to guarantee the realization of general needs. But we have to remember that the state does not have possibility of generating own income. The citizens have to give a part of their earned money, restricting their own expenditures. There exists the danger of too much financial charges. The prosperity of the country depends on the structure of expenditures. A wide range of public expenditures, especially social benefits can cause economic crisis. Without investment expenditures the country cannot develop. This article presents the situation of public funds in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 32-43